Analysing The Road Of Self-Efficacy Research In Indonesia - Alzhafirah Nadiyah; Mohammed Hasan Ali Al-Abyadh; Nicolette Roman; Fatih Ilhamsyah; Alrefi Alrefi (Pamomong: Journal of Islamic Educational Counseling, 2023)
Self-efficacy is an individual's subjective assessment of their ability to effectively navigate and surmount obstacles and achieve desired outcomes. It is a key element of motivation and can be facilitated through experiential learning, skill mastery, and positive reinforcement. It can also be augmented through interventions and techniques. The purpose of this study is to explore and analyse the direction of self-efficacy research in the last ten years in Indonesia to show its novelty. The method of analysis used is content analysis. The sample used was articles published on googlescholar. The data was extracted based on a review of the title, method, and research results. The findings of this study state that self-efficacy has an influence on personal, academic, and career fields in the Indonesian literature. Methodologically, correlation and multiple regression techniques were the most widely used methods for establishing relationships. Self-efficacy research is expected to contribute to future researchers examining self-efficacy with other psychological aspects with different research methods